2002
DOI: 10.1046/j.1467-7652.2003.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional control of nutrient partitioning during rice grain filling

Abstract: SummaryCereal grains accumulate carbohydrates, storage proteins and fatty acids via different pathways during their development. Many genes that participate in nutrient partitioning during grain filling and that affect starch quality have been identified. To understand how the expression of these genes is coordinated during grain development, a genomic approach to surveying the participation and interactions of all the pathways is necessary.Using recently published rice genome information, we designed a rice G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(124 citation statements)
references
References 39 publications
3
121
0
Order By: Relevance
“…Previous work by others and our own analyses (Supplemental Fig. 1) indicate that the false positive rate for the rice array is 0.5% (Zhu et al, 2003) or less (0.37%; Supplemental Fig. 1), with a 2-fold cutoff and approximately 1.9% with a 1.5-fold cutoff (Supplemental Fig.…”
Section: Expression Profiles Of Rice Aleurone Genes Reveal Patterns Omentioning
confidence: 70%
See 2 more Smart Citations
“…Previous work by others and our own analyses (Supplemental Fig. 1) indicate that the false positive rate for the rice array is 0.5% (Zhu et al, 2003) or less (0.37%; Supplemental Fig. 1), with a 2-fold cutoff and approximately 1.9% with a 1.5-fold cutoff (Supplemental Fig.…”
Section: Expression Profiles Of Rice Aleurone Genes Reveal Patterns Omentioning
confidence: 70%
“…All microarray experiments were done using the custom-built Genechip described by Zhu et al (2003). Preparation of cDNA and cRNA, fluorescent labeling, hybridization to the chip, and quality control steps were done exactly as described previously (Zhu et al, 2003).…”
Section: Rna Extraction and Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhanced resistance of the spl11 mutant to the two pathogens correlates with the constitutive expression of several defense-related genes and lesion development on Ubiquitination-mediated protein degradation in plant-microbe interactions 420 npg the leaves [80]. The constitutive activation of defense responses in the spl11 mutant was further confirmed when an array-based expression profiling was performed using the Sygenta rice gene chips that harbor nearly half of all rice genes [81] to analyze the impact of the spl11 mutation on the rice transcriptome. Comparison of the global transcripts between the wild-type plants and the spl11 mutant plants in three types of leaf tissues with different lesion development phenotypes revealed that the spl11 mutation causes significant changes in the rice transcriptome (data not shown).…”
Section: U-box-type E3 Ligases Are Newly Identified Members Of the Ubmentioning
confidence: 79%
“…OsENOD93-1 gene consists of three exons and two introns, encodes a 116 amino acids long protein. Zhu et al, 2003 revealed that OsENOD93-1 showed a high level of expression in root, especially at the panicle emergence stage. Bi et al, 2009 suggested that OsENOD93-1 gene significantly responded to both N induction and N reduction.…”
Section: Introductionmentioning
confidence: 99%